PENGARUH WORK-LIFE BALANCE DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN DI TOKO SINAR BANGUNAN KOTA PALOPO - Afry, Ahmad Faqih; Kasran, Muhammad; Samsinar, Samsinar (ITB AAS Indonesia Surakarta, 2024)
In a company, employees or human resources in the company must contribute and perform well for the company they work for. To improve an employee's performance and increase the company's success rate, the company's manager or leader must pay attention to supporting factors, one of which is Work-life Balance and Employee Engagement. The purpose of this study is to find out whether Work-life Balance and Employee Engagement have an impact on employee performance at Sinar Bangunan stores in Palopo City. This study took a sample from all Sinar Bangunan Palopo store staff, which amounted to 66 employees. The type of research is quantitative research. The Likert scale method is a data collection technique used. IBM SPSS Statistics version 25 is a data analysis technique used to process and test this study. This study shows that there is no influence of Work-life Balance on Employee Performance, there is a significant positive influence of Employee Engagement on Employee Performance, while Work-life Balance and Employee Engagement simultaneously have a positive impact on employee performance. Keywords : Work-life Balance, Employee Engagement, Employee Performance